Gaya Hidup Metrosexual Di Pekanbaru - Immanuel Frizth R; Achmad Hidir (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
Pekanbaru is one of the rapidly growing urban areas in the modernization era. The shift in lifestyle in the modernization era does not only affect women but also men's lifestyles. Some of the lifestyles of men that have changed in the current era of modernization are the way they look fashionable, smell good, clean, which is usually only owned by women. Men with this lifestyle are known as Metrosexuals. This research was conducted at a beauty clinic in Pekanbaru. The purpose of this research is to find out the metrosexual lifestyle from the frontstage and backstage sides. There were 5 subjects in this study, namely men who did facial treatments. The author uses accidental sampling method. Data instruments are observation, in-depth interviews and documentation. From the results of this study it can be concluded that the lifestyle of metrosexuals varies according to their preferences in using time and their preferences.